Development of Disposable Carbon Nanofibers Electrodes Supported on Filters. Issue 4 (24th November 2015) - Paramo, Ana Erica; Palmero, Susana; Heras, Aranzazu; Colina, Alvaro; Ibañez, David
Abstract: The purpose of this work is to develop simple and reproducible ways to fabricate carbon nanofibers (CNFs) electrodes. Disposable CNFs electrodes were fabricated after filtering CNFs through polytetrafluoroethylene filters (PTFE), using directly as electrodes these filters with the CNFs film. The electrochemical behaviour of CNFs/PTFE electrodes were tested with ferrocenemethanol and tris(2, 2′‐bypyridyl)dichlororuthenium(II) (Ru(bipy)3 2+ ). As a proof of concept of the analytical usefulness of the CNFs/PFTE electrodes, the study of vitamin B12 was carried out. Multivariate calibrate has been successfully used to determine vitamin B12 in a complex medium with vitamins B1 and B6 as interferents. Abstract :